Identifying non-adopters’ reason of using e-pharmacy in Indonesia from the benefit and perceived risk - Aflianto Perdana Putra; Ira Christie Wisandha; Jetro Junaidi Manalu; Jimmie Sugiono; Yohanes loppies; Yuniarti Sidik (Science Midwifery, 2023)
The growth of e-commerce in Indonesia is very fast, also being triggered by Covid-19 outbreak has been creating new habits to fulfill life necessities, including the way to purchase medicine online on the right e-commerce platform or online pharmacy. Inline, the government has tightened its policies to regulate the sale of drugs online in order to protect the public. This research aims to identify non-adopter’s reason of using e-pharmacy in Indonesia, which actually as an access to deliver their need for getting right medicines in this era. Using quantitative method by asking 323 respondents living in around Jakarta, Bogor, Depok, Tangerang, and Bekasi. And based on theory of Technology Acceptance Model or TAM, this research will integrate further, what factors that make non-adopters’ decide to use e-pharmacy (positive factor), and what factors make non-adopters decide not to use e-pharmacy (negative factor). This research suggests that perceived usefulness, perceived ease of use, trustworthiness, social influence and health literacy have closed correlation with the non-adaptors’ decision for e-pharmacy adoption. However, perceived risk is found to not directly affect non-adaptors’ decision for e-pharmacy adaptation. This study has produced results of the indication of perceived ease of use, intelligence, trust, health literacy and social influence have a positive effect on non-adopters' reasons for using e-pharmacy. Meanwhile, perceived risk has a negative effect on non-adopters' confidence in using e-pharmacy. Then, perceived ease of use has a positive effect on perceived usefulness and trust in using e-pharmacy.